2022
DOI: 10.1007/s00592-022-01918-8
|View full text |Cite
|
Sign up to set email alerts
|

There is no dose–response relationship between the amount of exercise and improvement in HbA1c in interventions over 12 weeks in patients with type 2 diabetes: a meta-analysis and meta-regression

Abstract: Aims Aerobic exercise is well recognised as an effective treatment for people with type 2 diabetes but the optimal amount of aerobic exercise to improve glycaemic control remains to be determined. Thus, the aim of this meta-analysis and meta-regression was to assess the impact of volume and intensity of aerobic exercise on glycaemic control. Methods Medline, Cochrane, Embase, and Web of Science databases were searched up until 15 December 2020 for the term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The DIAfit program was effective in improving body composition. The observed mean reduction in weight of 0.93 kg and waist circumference of 1.14 cm are similar to results found in some structured PA programs of similar duration without any dietary intervention and demonstrates the effects that can be achieved with this intensity and volume of PA (8,9,13). The waist circumference, but not weight reduction observed in our study is similar to the changes observed in one of the largest and longest randomized trial (Look AHEAD) assessing the impact of a combined very intensive lifestyle intervention on weight loss, 8 years after the intervention (44).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The DIAfit program was effective in improving body composition. The observed mean reduction in weight of 0.93 kg and waist circumference of 1.14 cm are similar to results found in some structured PA programs of similar duration without any dietary intervention and demonstrates the effects that can be achieved with this intensity and volume of PA (8,9,13). The waist circumference, but not weight reduction observed in our study is similar to the changes observed in one of the largest and longest randomized trial (Look AHEAD) assessing the impact of a combined very intensive lifestyle intervention on weight loss, 8 years after the intervention (44).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, flexibility and balance training are recommended for older adults with type 2 diabetes (7). Structured PA training programs have been performed and shown to be effective in improving glycaemic control, aerobic fitness and reducing other cardiovascular risk factors in patients with type 2 diabetes (8)(9)(10)(11). Although the efficacy of intensive PA interventions in specialized research and clinical centres has been proven, an important challenge remains in translating PA interventions into pragmatic programs in real-life settings.…”
Section: Introductionmentioning
confidence: 99%
“…The ADA recommends the measurement of HbA1c as the standard for monitoring diabetes, as it is directly correlated with average plasma glucose concentrations [66]. Numerous studies showing a decrease in blood glucose concentrations support the evidence provided by the HbA1c biomarker that exercise programs have a beneficial effect on glycemic control in diabetic [65] and non-diabetic subjects [62].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that HbA1c levels may reach a plateau between 8 and 12 weeks [ 64 ], confirming that <12-week physical activity interventions are more effective in reducing HbA1c among non-diabetics, as stated by Cavero-Redondo et al [ 62 ]. On the other hand, Wrench et al [ 65 ] observed a significant reduction in HbA1c values after >12 weeks of aerobic exercise in diabetic subjects. Our results are in line with those shown by Wrench et al [ 64 ], probably because 71% of our subjects had insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effects of physical exercise on HbA1c and BMI are found to be associated with interventions lengths, with an incremental decrease in HbA1c of 0.009 to 0.043% for each additional week of physical training, underscoring the importance of adherence to exercise for a sustained lifestyle change in achieving health improvements ( 41 ). However, a recent meta-analysis suggests that interventions longer than 12 weeks do not induce additional benefits on HbA1c ( 54 ). Taken together the results of the included studies reinforce the need for regularity and spacing between physical training sessions, but also the need for progression of the intervention intensity for adequate management and glycemic control ( 55 ).…”
Section: Discussionmentioning
confidence: 99%